2016
DOI: 10.1128/aem.01186-15
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Characteristics of Deep-UV Light-Emitting Diodes and Their Application To Control Foodborne Pathogens

Abstract: b Low-pressure mercury UV (LP-UV) lamps have long been used for bacterial inactivation, but due to certain disadvantages, such as the possibility of mercury leakage, deep-UV-C light-emitting diodes (DUV-LEDs) for disinfection have recently been of great interest as an alternative. Therefore, in this study, we examined the basic spectral properties of DUV-LEDs and the effects of UV-C irradiation for inactivating foodborne pathogens, including Escherichia coli O157:H7, Salmonella enterica serovar Typhimurium, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 32 publications
0
54
1
Order By: Relevance
“…The value of each point was divided by the maximum fluence rate and averaged to obtain the petri factor. Modified UV intensity was calculated by multiplying the maximum intensity by the petri factor, so that averaged UVC LED fluence rate was represented by the calculated value (21)(22)(23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of each point was divided by the maximum fluence rate and averaged to obtain the petri factor. Modified UV intensity was calculated by multiplying the maximum intensity by the petri factor, so that averaged UVC LED fluence rate was represented by the calculated value (21)(22)(23).…”
Section: Resultsmentioning
confidence: 99%
“…For example, their small size makes them easy to incorporate into a sterilization system and, above all, they do not contain mercury, thus alleviating risks of human and environmental toxicity (20). Shin et al reported that UVC LED intensity was not influenced by temperature change and no warm-up time was required for maximum intensity output, whereas LP lamps had decreased output intensity at low temperature and a warm-up time of about 5 min was required (21). In addition, UVC LEDs showed much higher inactivating efficacy against Escherichia coli O157:H7, Salmonella enterica serovar Typhimurium, and Listeria monocytogenes than LP lamps at the same dosages with intensity adjustment (22).…”
mentioning
confidence: 99%
“…; Shin et al . ). UV‐C LED irradiation (266 nm; irradiance 4 μ W cm −2 ) reduced the viability of Escherichia coli O157:H7 by 6 log units at 0·5 mJ cm −2 .…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, a versatile UV source has been provided by the development of light-emitting diodes (LEDs), which yield constant illumination at a specific wavelength and do not contain mercury. Lightemitting diodes are also advantageous because of their durability and low heat generation (Shin et al 2016). A LED illumining UV-C light (266 nm or 275 nm), which is defined as radiation with wavelengths 200-280 nm and has traditionally been used as an effective germicidal disinfectant, exhibited high bactericidal activity Shin et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Also, UV-LEDs emit high-intensity light as soon as they are turned on; in other words, there is no warm-up time. Furthermore, Shin et al (4) demonstrated that UV-LEDs contain no mercury and yield a consistent irradiation output regardless of temperature, which makes them effective even under refrigeration. Although UV mercury lamps emit only one wavelength (254 nm), UV-LEDs can be configured to emit certain target wavelengths.…”
mentioning
confidence: 99%